Ethical Issues Are Transversal and Habitual: Ethical Dimensions in Training and Practice for Community Psychology - Pasmanik-Volochinsky, D; Winkler-Muller, M (UNIV CHILE, CENTRO INTERDISCIPLINARIO ESTUDIOS BIOETICA, 2012)
Community psychology has suffered huge transformations associated to a historical and contextual process in our country, involving a series of ethical issues which have not been dealt with both in training and deontological discipline. The aim of this research was to inquire the perception of students and professionals with respect to ethics in practice and training in community psychology. Our participants were Chilean experts, students in practice and students of two Master programs in community psychology with three data sources: Delphi panel (8 experts), in-depth interviews (7 master students), and focal groups (20 students in community practice). By applying the principles of the theory empirically based, data analysis showed the identifications of four topics: ethical notion, types of ethical situations, ethical training and deontology. Among the results, the simultaneous character of ethical dimensions "transversal and habitual" as well as "vague" was highlighted in the discourse of our participants. Considering concrete situations, these identified general ethical principles, which was verbalized as Respect for the Other and Autonomy.